Modified minimally invasive chevron osteotomy versus traditional incision chevron osteotomy - Run Tang; Jie Yang; Xiao Jun Liang; Yi Li; JunHu Wang; MiaoLuo Jin; Yang Du; Tong Lu; YiXiang Hao (BMC Musculoskeletal Disorders)
Abstract Purpose This study aimed to compare modified minimally invasive chevron osteotomy (MIC group) and traditional incision chevron osteotomy (TIC group) for correction of mild to moderate hallux valgus deformity. Methods This retrospective study enrolled 42 patients (60 feet) with mild to moderate hallux valgus deformities who were treated with modified MIC osteotomy or TIC osteotomy between January 2020 and June 2021. The patients were divided into the MIC and TIC groups according to whether the treatment received was minimally invasive. The MIC group included 20 patients (28 feet), comprising 1 male and 19 female patients; aged 37.15 ± 14.60 years, with mild hallux valgus deformity in 12 cases (14 feet) and moderate hallux valgus deformity in 8 cases (14 feet). In the TIC group comprising 22 patients (32 feet), including 1 male and 21 female patients, aged 40.95 ± 11.60 years, mild and moderate hallux valgus deformities were observed in 10 (18 feet) and 12 cases (14 feet), respectively. Preoperatively and at the last follow-up, the American Orthopedic Foot and Ankle Society (AOFAS) hallux, lesser toe score, and visual analog scale (VAS) pain were used to evaluate clinical efficacy. The hallux valgus angle (HVA), 1–2 metatarsal angle (1-2IMA), and distal metatarsal articular angle (DMAA) were measured and compared on the weight-bearing X-ray film of the foot preoperatively and postoperatively. At the last follow-up, recurrence of hallux valgus deformity, hallux adduction deformity, metatarsal head necrosis, metastatic plantar pain, and other complications were recorded. Results All 42 patients were followed up, and the follow-up time of the MIC group was 24.70 ± 6.63 months; The follow-up time of the TIC group was 22.82 ± 6.12 months, and there was no significant difference in follow-up time between the two groups (P > 0.05). One patient in the MIC group experienced pain in the dorsal side of the front foot postoperatively; one patient in the TIC group had a superficial infection of the incision postoperatively. There were no significant differences in age, gender, side classification, course of the disease, degree of hallux valgus deformity, and postoperative complications between the two groups (P > 0.05). The AOFAS scores, VAS, HVA, 1-2IMA, and DMAA in the MIC group improved from 54.61 ± 7.60, 4.50 ± 0.79, 28.38° ± 5.02°, 12.88° ± 1.50°, 12.03° ± 1.88°preoperatively to 89.93 ± 4.96, 2.04 ± 1.10, 10.27° ± 1.68°, 7.49° ± 0.95° and 7.83° ± 1.33° at the last follow-up, the difference was statistically significant (P < 0.05); the AOFAS score, VAS, HVA, 1-2IMA, and DMAA of the TIC group improved from 57.31 ± 7.59, 4.34 ± 0.70, 28.45° ± 4.47°, 12.88° ± 1.50°, 12.16° ± 1.81° preoperatively to 87.97 ± 5.96, 2.00 ± 1.11, 10.99° ± 2.25°, 7.49° ± 0.95°, and 8.25° ± 1.12° at the last follow-up, the difference was statistically significant (P < 0.05), but there was no significant difference in AOFAS score, VAS, HVA, 1-2IMA, and DMAA between the two groups (P > 0.05). The incision length of the MIC group was 2.06 ± 0.20 cm, and the incision length of the TIC group was 5.04 ± 0.54 cm, which was statistically significant (P < 0.05). Conclusion Whether it is modified minimally invasive chevron osteotomy or traditional incision chevron osteotomy, mild and moderate hallux valgus deformity is effectively treated, and the clinical efficacy and imaging results after surgery are significantly improved. Compared with traditional incision chevron osteotomy, the modified minimally invasive chevron osteotomy has a smaller incision and less trauma for mild to moderate hallux valgus.